Comparative Neuroanatomy of the Lateral Accessory Lobe in the Insect Brain - Namiki, Shigehiro; Kanzaki, Ryohei (Frontiers in Physiology, 2016)
The lateral accessory lobe (LAL) mediates signals from the central complex to the thoracic motor centers. The results obtained from different insects suggest that the LAL is highly relevant to the locomotion. Perhaps due to its deep location and lack of clear anatomical boundaries, few studies have focused on this brain region. Systematic data of LAL interneurons are available in the silkmoth. We here review individual neurons constituting the LAL by comparing the silkmoth and other insects. The survey through the connectivity and intrinsic organization suggests potential homology in the organization of the LAL among insects.